C.S. Lewis - Loomis, S. author. aut Link
XI, 234 p.
Keywords: Collaborating with the genius of C.S. Lewis, and particularly his brilliant work The Abolition of Man, the authors offer a multi-facetted, interdisciplinary investigation of perennial questions that impact human development and freedom.